Penggunaan Biomassa Limbah Pertanian sebagai Bahan Bakar pada Mini Boiler Tipe Pipa Api 3 Pass - Umi Hanifah; Novita Dwi Susanti; Moeso Andrianto (agriTECH, 2019)
The use of mini boilers in SMEs is one strategy to improve the efficiency of energy use. This is based on the results of previous work. The use of 3-phase fire tube mini boiler type in tofu SMEs with gas fuel or wood pellets can increase the efficiency of fuel energy use for cooking to about 14.03%–25.58%, save time to about 50%–53%, and save fuel costs for cooking by 44%–45%, compared to cooking tofu using a gas stove. This study was conducted to analyze the performance of 3-phase fire tube mini boiler type with wood pellets or coconut shells as fuel. The testing of mini boilers was conducted related to the capacity/ quantity and quality of steam produced, the energy efficiency of the mini boiler, and the specific costs of steam production (IDR fuel / kJ steam produced) in each type of fuel. The results showed that this mini boiler had a higher value of steam production capacity, steam temperature, steam pressure, and energy efficiency, and specific costs of steam production by using wood pellets as fuel. It also means that using coconut shells as fuel was cheaper, but it gave a lower performance.